2020
DOI: 10.1109/access.2020.3016760
|View full text |Cite
|
Sign up to set email alerts
|

An Authorized Public Auditing Scheme for Dynamic Big Data Storage in Cloud Computing

Abstract: Nowadays, to utilize the abundant resources of cloud computing, most enterprise users prefer to store their big data on cloud servers for sharing and utilization. However, storing data in remote cloud servers is out of user's control and exposes to lots of security problems such data availability, unauthorized access and data integrity, among which data integrity is a challenging and urgent task in cloud computing. Many auditing schemes have been proposed to check the integrity of data in cloud, but these sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…One of them is that these auditing systems cannot determine which block is corrupt where the data is not synchronized. The other issue is that no efficient authenticated data structure can assist with effective auditing as data is updated regularly (Yu et al, 2020). Yu et al (2020) suggested a public auditing system for dynamic big data storage in cloud computing to address the issues.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…One of them is that these auditing systems cannot determine which block is corrupt where the data is not synchronized. The other issue is that no efficient authenticated data structure can assist with effective auditing as data is updated regularly (Yu et al, 2020). Yu et al (2020) suggested a public auditing system for dynamic big data storage in cloud computing to address the issues.…”
Section: Overviewmentioning
confidence: 99%
“…The other issue is that no efficient authenticated data structure can assist with effective auditing as data is updated regularly (Yu et al, 2020). Yu et al (2020) suggested a public auditing system for dynamic big data storage in cloud computing to address the issues. Therefore, Yu et al (2020) created a dynamic index table that does not include any element movement during deletion or insertion update operations.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The data users utilize the higher and open scalable API to store the pictures, files, video, etc. The data users delete their original larger data after outsourcing from their server of local storage to save storage space [5]. The storage of data on cloud servers without possessing the original data will result in many security and privacy issues.…”
Section: Introductionmentioning
confidence: 99%